THE DYNAMIC PROPERTIES OF ZIRCON STUDIED BY SINGLE-CRYSTAL X-RAY DIFFRACTION AND RAMAN SPECTROSCOPY - Kolesov B.A.; Geiger C.A.; Armbruster T. (My University, 2001)
An investigation of the dynamic properties of synthetic non-metamict zircon, ZrSiO4, was undertake n using X-ray single-crystal diffraction and polarized single-crystal Raman spectroscopy. The X-ray results at room temperature show that the Zr cation located on the triangular dodecahedral site is tightly bonded. The atomic dis- placement parameters from different crystals and refinements on zircon are compared and shown to be different. This is probably a result of experimental problems associated with extinction and/or slight degrees of metamictization in natural samples. A calculation of the librational motions of the rigid SiO4 tetrahedron give a mean-square libration of 3.3(3) degree2 along the a axes and 6.9(6) degree2 along the c axis. The Raman spectrum shows some unusual fea- tures, such as the low wave number SiO4 bending motion, u 2, at 266 cm-1, that can be explained by the structural prop- erties of zircon. The structure is characterized by open 'channels ' running parallel to (001) and they influence the energies of the SiO4 bending modes depending upon their symmetries. The Raman modes differ strongly in intensi- ty and this can be explained by vibrational interactions with the electronic state of Zr4+. In contrast to garnet, which shares a few structural similarities with zircon, the Zr cation residing in the large dodecahedral site shows little dynamic disorder. In addition, all the external modes in zircon are harmonic in comparison to a few modes in pyrope garnet, for example, that soften with decreasing temperature.
Keywords: zircon; X-ray diffraction; lattice dynamics; Raman spectroscopy